Nurses in advanced roles in primary care Policy levers for implementation - Maier, Claudia ca. 20./21. Jh (OECD Health Working Papers, 2017)
Many OECD countries have undergone reforms over the past decade to introduce advanced roles for nurses in primary care to improve access to care, quality of care and/or to reduce costs. This working paper provides an analysis of these nurse role developments and reforms in 37 OECD and EU countries. Four main trends emerge: 1) the development in several countries of specific advanced practice nursing roles at the interface between the traditional nursing and medical professions; 2) the introduction of various new, supplementary nursing roles, often focused on the management of chronic conditions; 3) the rise in educational programmes to train nurses to the required skills and competencies; and 4) the adoption of new laws and regulations in a number of countries since 2010 to allow certain categories of nurses to prescribe pharmaceuticals (including in Estonia, Finland, France, Netherlands, Poland and Spain)